Penyakit Layu Bakteri Stewart pada Jagung di Bali - I Gede Rai Maya Temaja; G.N. Alit Susanta Wirya; Ni Made Puspawati; Khairun Nisak Syahdu (Jurnal Fitopatologi Indonesia, 2017)
Stewart’s wilt is a serious disease of sweet corn (Zea mays). The typical symptoms of the disease are pale-green to yellow linear streaks parallel to the veins. The symptoms were observed on sweet corn in Denpasar, Tabanan, Gianyar, and Karangasem areas during a survey in 2015. Pathogen detection based on a polymerase chain reaction was carried out using total DNA obtained from symptomatic leaf samples and the pairs of primers, CPSL1/CPSR2c. The expected sized (~1100 bp) amplicon was detected in samples from Denpasar. Sequence analysis confirmed that Stewart’s wilt disease symptoms are caused by Pantoea stewartii subsp. stewartii. Nucleotide sequence and phylogenetic analysis showed that P. stewartii subsp. stewartii from Bali has high homology (98.97-99.08 %) and placed in the same clade with isolates from Canada, USA and Japan. This is the first report of P. stewarti subsp. stewartii on corn in Bali.